Prevalence of seed-borne fungi of different vegetables seeds in Bangladesh - Mohanto, Ratan Chandro; Shahriar, Saleh Ahmed; Ahmmed, Abu Noman Faruq; Nishi, Farzana Afrin; Khatun Eaty, Most. Nurjahan (Research in Biotechnology, 2019)
The experiment was carried out to evaluate the prevalence of seed-borne fungi of ten selected vegetables seeds e.g. amaranth, Indian spinach, bottle gourd, sweet gourd, snake gourd, okra, bitter gourd, cucumber, brinjal and country bean. Untreated and unknown grower’s bulk vegetables loose seeds were collected from three different seed sources of Rangpur district, Bangladesh e.g. New Bangla Seeds; Islam Seeds and Rafiq Traders. The high level of infection was found in the seeds of Rafiq Traders and the lowest infection was observed in the seeds of New Bangla Seeds. Islam Seeds provided moderate infection of fungal pathogens. Fungal fruiting bodies, mycelium (white and cottony) and acervuli were found under microscopic observation. The observed physical abnormalities viz. deformed, shrinkage, swelling, spotted and undersized seeds were recorded from all seed sources. Aspergillus flavus, Aspergillus niger, Fusarium sp., Alternaria sp., Chaetomium sp., Rhizopus sp. and unidentified bacteria were observed by blotter method. Aspergillus flavus showed maximum incidence (9.0%) in okra and minimum incidence (5.50%) in brinjal. Aspergillus niger was the most predominant (9.0%) in sweet gourd and minor (5.0%) in bottle gourd. Incidence of Fusarium sp. (5.0%) and Rhizopus sp. (8.75%) were predominant in bottle gourd. The lowest incidence for Fusarium sp. (2.50%) and Rhizopus sp. (3.0%) were found in snake gourd and amaranth respectively. The highest incidence of Alternaria sp. (4.75%) and Chaetomium sp. (9.0%) were found both in sweet gourd and bitter gourd but minimum incidence of Alternaria sp. (2.0%) and Chaetomium (3.75%) were recorded in amaranth and okra respectively. In case of unidentified bacteria, maximum incidence (4.50%) was recorded in bottle gourd.